Biodiversity database / Agan Adun Shashi Mohan - Agan Adun, Shashi Mohan (2013)

(untitled)
There is a growing interest in academia to provide biodiversity data to both the scientific community and the public. Biodiversity Informatics Laboratory Portal was developed to provide useful information to both scientists, who can easily navigate and find all parasite related resources in one place, and bioinformaticians, who are provided with interoperable resources containing data which can be mined and integrated. This thesis demonstrates how Web service technology provide the ability to create a dynamic integration of multiple heterogenous databases while maintaining the existing database schemas and not losing control over the administration of the databases.